The Effect Of Relaxing A Deep Breath On Anxiety Levels - Sajidah, Holila; Khairunnisa, Salwa; Nabila, Cahya (Jurnal KESANS : Kesehatan dan Sains, 2021)
Emotions and breathing are closely linked in a complex feedback loop. Understanding this interrelationship between breathing and emotions is critical to better understanding how to deal with anxiety, stress, depression, and emotional disturbances. During emotional attacks and anxious states, the autonomic nervous system triggers physiological variables such as heart rate, breathing, blood pressure, hormonal secretions, palpitations, gastrointestinal functions suddenly increase as a result of which the normal social and behavioral functions of the individual are disturbed. It is generally believed that deep breathing, practiced with various techniques, such as qigong and yoga, can promote relaxation. Source searches were carried out on the online portal of journal publications as many as 10 sources from Medscape, Google Scholar, National Center for Biotechnology Information (NCBI) with the keywords anxiety, relaxation, and deep breathing. Deep breathing relaxation has been shown to be effective in reducing the perception and symptoms of anxiety. Deep breathing offers several advantages over conventional therapies currently used to treat anxiety problems. These advantages include a non-pharmacological approach, safety, minimal space requirements, ease of learning, and ease of practice.